Early stopping versus continued retrievals after failed recanalization: associated factors and implications for outcome - Kniep, Helge; Meyer, Lukas; Broocks, Gabriel; Bechstein, Matthias; Heitkamp, Christian; Winkelmeier, Laurens; Geest, Vincent; Faizy, Tobias D.; Feyen, Ludger; Brekenfeld, Caspar; Flottmann, Fabian; McDonough, Rosalie V.; et al. (Journal of neuroInterventional surgery, 2024)
Background Successful recanalization defined as modified Thrombolysis in Cerebral Infarction Score (mTICI) ≥2b is not achieved in 15%-20% of patients with acute ischemic stroke. This study aims to identify patient-specific factors associated with early stopping without successful recanalization. We hypothesized that the probability of the decision for early stopping during mechanical thrombectomy (MT) is higher in patients with an unfavorable prognosis. - Methods All patients enrolled in the German Stroke Registry (GSR) between June 2015 and December 2021 were screened. Inclusion criteria were stroke in the anterior circulation and availability of relevant clinical data. For each retrieval attempt 1-3, patients with stopping and failed reperfusion (mTICI <2b) were compared with all patients with continued retrieval attempts using descriptive statistics and multivariable logistic regression. - Results Our study included 2977 patients, 350 (12%) of which had early stopping. Higher pre-stroke Modified Rankin Scale (mRS) score (adjusted odds ratio (aOR) =1.20 (95% confidence interval (CI): 1.09; 1.32), P<0.001), higher age (aOR=1.01 (1.00; 1.02), P=0.017) and distal occlusions (aOR=1.93 (1.50; 2.47), P<0.001) as well as intraprocedural dissections/perforations (aOR=4.61 (2.95; 7.20), P<0.001) and extravasation (aOR=2.43 (1.55;3.82), P<0.001) were associated with early stopping. In patients with unsuccessful recanalization (n=622), the number of retrieval attempts (aOR=1.05 (0.94; 1.18), p=0.405) was not associated with unfavorable outcomes (90d-mRS>3). - Conclusion The probability of early stopping was higher in patients with clinical conditions associated with: a) Favorable prognosis and assumed lower impact of recanalization success on functional status, such as distal occlusions; and b) Unfavorable prognosis, such as higher age and reduced pre-stroke functional status. Adverse events during the procedure increased the probability of early stopping. The number of recanalization attempts did not increase the risk of unfavorable outcome for patients with persistent occlusion, supporting the decision for continuation of retrieval attempts.